PENGELOMPOKAN PASIEN DEMAM BERDARAH RSUD dr. SOEHADI PRIJONEGORO DENGAN METODE ANALISIS KELAS LATEN - Nurhayati, Noviana; Mukid, Moch. Abdul; Ispriyanti, Dwi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
The degree of disease dengue patients in early at the hospital is latent or unknown directly. Therefore it needs an indicator variables such as the examination of hematocrit, leukocytes and platelets to classify patients with dengue fever into classes according to the degree of disease. In this study, the method used to classify patients with dengue fever is a latent class analysis method. The purpose of this study is to establish a latent class model and describes profile of the class on cases of grouping dengue fever patients in dr. Soehadi Prijonegoro Sragen. The results from latent class analysis showed that the latent class model formed is two latent class model. There are two classes formed is class 0 for disease dengue infection with danger signs have criteria a normal hematocrit, abnormal leukocyte and platelet abnormal and class 1 for disease dengue infection without signs of danger have criteria a normal hematocrit, normal leukocytes and normal platelets.Keyword : dengue fever, latent class analysis, latent variables